2013
DOI: 10.1097/pai.0b013e318283980a
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype of Myxopapillary Ependymomas

Abstract: Myxopapillary ependymoma (MPE) is a slow-growing tumor occurring almost exclusively in the region of conus medullaris, cauda equina, and filum terminale. On microscopic examination, some of these tumors show solid sheets of cells with an epithelioid morphology mimicking a metastatic carcinoma. Several immunohistochemical studies addressed this issue with discordant results. We report the immunohistochemical findings of 9 additional cases of MPE. From 2004 to 2011, a total of 9 cases of MPE were recorded in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…16,17 MPE is usually positive for CD99, CD56, and GFAP. 18 Podoplanin is not expressed in our case. This is different from the expression pattern previously reported.…”
Section: Discussioncontrasting
confidence: 46%
“…16,17 MPE is usually positive for CD99, CD56, and GFAP. 18 Podoplanin is not expressed in our case. This is different from the expression pattern previously reported.…”
Section: Discussioncontrasting
confidence: 46%
“…Brachyury is also negative in myxopapillary ependymoma, a diagnostic consideration in sacral locations . Myxopapillary ependymoma is positive for S‐100 and GFAP, and can show at least focal cytokeratin positivity, thus brachyury is useful in the distinction between myxopapillary ependymoma and chordoma. Myoepithelial tumors of soft tissue typically show heterogeneous expression of S‐100, GFAP, keratin, EMA, and SMA, and may mimic chordoma when a myxoid stroma is predominant.…”
Section: Discussionmentioning
confidence: 99%
“…Brachyury staining is absent in soft tissue mixed tumor/myoepithelioma, and careful histologic examination will also help distinguish myoepithelial neoplasms from chordoma. Lastly, the survey studies examining brachyury expression in large numbers of neoplasms have reported an absence of staining in the majority of entities tested, including osteosarcoma, synovial sarcoma, chondromyxoid fibroma, chondroblastoma, extraskeletal myxoid chondrosarcoma, myxoid liposarcoma, rhabdomyosarcoma, pleomorphic adenoma, mucoepidermoid carcinoma, melanoma, and urothelial, breast, and ovarian carcinoma . While one study reported brachyury expression in non‐neoplastic testis and a second study found positive staining in a small subset of germ cell tumors, a subsequent larger series reported no staining in 111 germ cell tumors and non‐neoplastic testis samples …”
Section: Discussionmentioning
confidence: 99%
“…Our aim was to test other IHC markers that have been studied in non-giant cell ependymomas and that could possibly be extrapolated to our case. Based in a study published by Lamzabi et al [21] in myxopapillary ependymomas that expressed CD99 in all cases and CD56 was diffusely positive in 88% cases, we attempted the technique. Other IHC studies have analyzed the expression of bcl-2, p53 and cyclin D1 in ependymomas and they appear to act as prognostic predictors although results are discordant [22].…”
Section: Discussionmentioning
confidence: 99%